Crash risk and aberrant driving behaviors among bus drivers: The role of personality and attitudes towards traffic safety. (June 2015) - Mallia, Luca; Lazuras, Lambros; Violani, Cristiano; Lucidi, Fabio
Highlights: This is one of the first studies that assessed a model of personality, attitudes and aberrant driving behaviors (i.e., violations, driving lapses and errors) in bus drivers. Altruism, excitement seeking, and normlessness directly predicted attitudes towards traffic safety. Positive attitudes towards traffic safety were negatively associated with self-reported aberrant driving behaviors. Self-reported violations predicted accident risk of bus drivers. Hostility and anxiety traits directly predicted aberrant driving behaviors, thus, highlighting the role of individual differences in crash risk. Abstract: Several studies have shown that personality traits and attitudes toward traffic safety predict aberrant driving behaviors and crash involvement. However, this process has not been adequately investigated in professional drivers, such as bus drivers. The present study used a personality–attitudes model to assess whether personality traits predicted aberrant self-reported driving behaviors (driving violations, lapses, and errors) both directly and indirectly, through the effects of attitudes towards traffic safety in a large sample of bus drivers. Additionally, the relationship between aberrant self-reported driving behaviors and crash risk was also assessed. Three hundred and one bus drivers (mean age = 39.1, SD = 10.7 years) completed a structured and anonymous questionnaire measuring personality traits, attitudes toward traffic safety, self-reported aberrant driving behaviors (i.e., errors, lapses, and traffic violations), and accident risk in the last 12 months. Structural equation modeling analysis revealed that personality traits were associated to aberrant driving behaviors both directly and indirectly. In particular altruism, excitement seeking, and normlessness directly predicted bus drivers' attitudes toward traffic safety which, in turn, were negatively associated with the three types of self-reported aberrant driving behaviors. Personality traits relevant to emotionality directly predicted bus drivers' aberrant driving behaviors, without any mediation of attitudes. Finally, only self-reported violations were related to bus drivers' accident risk. The present findings suggest that the hypothesized personality–attitudes model accounts for aberrant driving behaviors in bus drivers, and provide the empirical basis for evidence-based road safety interventions in the context of public transport.